Phonemic Transcription Symbols in EFL Teaching : Focus on Finnish Fourth Graders - Ströömi, Elina (My University, 2026)
This thesis explores the use of phonemic transcription symbols in Finnish EFL teaching. Previous research has shown that pronunciation is an often-overlooked element in EFL lessons, and symbols of phonemic transcription even more so. This study set out to examine whether primary school English students in Finland recognise transcription symbols. Another aim was to measure how well they are able to produce the sounds corresponding to the symbols. The study also explored the use of transcription symbols in teaching and teachers’ reasons for including these in or omitting these from lesson plans. The study was limited to year four students of English, in seven primary schools in Southwestern Finland. There were a total of 68 analysed participants. Three sounds and symbols were chosen for the experiment: the sibilant /ʃ/, the fricative /θ/, and the affricate /tʃ/. The test participants were studied through a researcher generated protocol, where they were shown a two-part elicitation presentation. One part included pictures of words containing the sounds of interest, the other non-words containing the same sounds. Participant responses were recorded and then analysed acoustically. The study also comprised an exercise book observation portion, where the completion rates were logged for four transcription symbol-based exercises in the participants’ exercise books. In addition, survey answers were collected from teachers regarding the use of phonemic transcription in their teaching and motivations behind use or non-use. The figures of central tendency from the elicitation tasks indicated that the participants were uniformly unfamiliar with the transcription symbols used in the non-words. They were, however, able to produce two of the three sounds with relative ease in the picture-based task. The sound /θ/ was noticeably more difficult than /ʃ/ and /tʃ/ in both tasks. The exercise book observation revealed that the completion rate of pronunciation exercises has a tendency to fall as the school year progresses. There was notable difference between the students of different teachers as well as variation in teachers’ practices and opinions. The main conclusion was that primary school students are not familiar with transcription symbols, despite having material related to them in their books and working on some of the material throughout the year. Another conclusion possibly yielding practical implications was that teachers tend to consider the use of phonemic transcription as extra content, and as such disposable when prioritisation is needed. Some form of reform regarding the use of transcription symbols in primary school EFL teaching appears to be needed, as the inclusion of these symbols in teaching materials appear currently not to be serving their purpose.
Keywords: second language acquisition, pronunciation, phonemic transcription, curriculum, teaching materials